Analysis Logistic Information Systems and Waiting Line Methods on Lion Parcel Customer Satisfaction During Covid-19 (2020-2021) - Erny Sulistyaningsih; Liauwuthor, Johanes Kurniawan; Nurcahyo, Ariyo Adi; Khotimah, Maulidiyah Usnul (Dinasti International Journal of Management Science, 2024)
This study assesses customer satisfaction with Lion Parcel during the 2020-2021 COVID-19 period, noting a substantial surge in orders during the pandemic and peak seasons. The research explores the potential of a Logistics Information System as a broader communication network for companies to send and receive information. Additionally, it employs the Waiting Line Method to address customer queue service issues. The study, involving 100 respondents categorized by gender, age, and occupation, utilizes quantitative methods with SmartPLS version 4.0. The analysis reveals that the Average Variance Extracted (AVE) values for the Logistics Information System (X1), Waiting Line Method (X2), and Customer Satisfaction (Y) exceed the 0.5 threshold, with values of 0.693, 0.625, and 0.829, respectively. The R-Square value of 0.711 suggests that all exogenous latent constructs collectively influence Customer Satisfaction (Y) by 71% in this study and 29% were influenced by other factors.